2023
DOI: 10.3390/life13051165
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile, Antioxidant, Antimicrobial, and Antidiabetic Activities of Ajuga iva (L.)

Abstract: In Morocco, many applications in ethnomedicine on Ajuga iva (L.) have been recognized as able to treat various pathologies such as diabetes, stress, and microbial infections. The objective of this work is to carry out phytochemical, biological, and pharmacological investigations on the extracts of Ajuga iva leaves in order to confirm its therapeutic effects. The phytochemical screening carried out on the different extracts of Ajuga iva showed its richness in primary (lipids and proteins) and secondary metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 110 publications
(157 reference statements)
1
2
0
Order By: Relevance
“…Importantly, no growth of Penicillium was observed in plates treated with the methanol extract of the sample collected from Aazzaba. The findings obtained from the present study are consistent with those reported by Saidi et al 18 In the same context, Makni et al observed that methanol extract was the most effective against Aspergillus clavatus, Aspergillus niger, and Fusarium sp., with inhibition zones of 11, 10, and 18 mm, respectively. 30 The extracts obtained from Ajuga iva exhibited the least potent antifungal activity against Candida albicans with an inhibition zone of 11 mm.…”
Section: Antifungal Activity Of Ajuga Iva Extractssupporting
confidence: 93%
See 1 more Smart Citation
“…Importantly, no growth of Penicillium was observed in plates treated with the methanol extract of the sample collected from Aazzaba. The findings obtained from the present study are consistent with those reported by Saidi et al 18 In the same context, Makni et al observed that methanol extract was the most effective against Aspergillus clavatus, Aspergillus niger, and Fusarium sp., with inhibition zones of 11, 10, and 18 mm, respectively. 30 The extracts obtained from Ajuga iva exhibited the least potent antifungal activity against Candida albicans with an inhibition zone of 11 mm.…”
Section: Antifungal Activity Of Ajuga Iva Extractssupporting
confidence: 93%
“…The phytochemistry of the herb revealed the presence of several active compounds, such as ferulic acid, quercetin, coumaric acid, and apigenin-7-(2-O-apiosylglucoside), which are well known for their antimicrobial properties. 18 Ferulic acid exhibited interesting antifungal activity against Candida albicans by altering the morphology and internal structure of the cell surface, resulting in damage to the integrity of the cell and leakage of its contents. 32 The combination of ferulic acid and caspofungin was found to be effective against C. albicans by inducing apoptosis.…”
Section: Antifungal Activity Of Ajuga Iva Extractsmentioning
confidence: 99%
“…The hydrogen potential provides information regarding the assimilation of nutrients by plants ( Saidi et al, 2023 ). In the present work, the abrialis and L. stoechas ranged from 4.96 to 5.94, respectively.…”
Section: Resultsmentioning
confidence: 99%